EFFECT OF APPLICATION TREAEED WATER AND DRY SLUDGE ON SIIL CONTAMINATION WITH PATHOGENIC BACTREIA - & Abd Alhameed, Shaker (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
Research was conducted to assess the effect of treated waste water and dry sludge application on soil contamination by some pathogenic bacteria such as Pseudomonas aeruginosa , Fecal coliform and Fecal streptococci, which used as an indicator organisms for soil contamination by bathogenic bacteria. Composting sludge (T2) and non composting dry sludge (T1) applied to soil to assess the effect of compost of sludge on the number of pathogenic bacteria and soil contamination . Research consisted to identification and enumeration. The three pathogenic bacteria were examined at the mid and end of cultivation season. Factorial experiment with three replicate, using waste water treatment (W2) as a source of irrigation water, compared with tap water (W1).Composting sludge(T2) and non-composting sludge (T1), added and mixed with soil in three different levels 0, 30 , 60 ton .ha-1 .Pancium milicine was cultivated in pots weighted 10 Kg of silty clay loam soil. Results showed that the number of pathogenic bacteria Pseudomonas aeruginosa, Fecal coliform and Fecal streptococci. Were increased significantly with soil irrigated with waste water treatment, giving 5.88, 5.48 and 5.37 log cfu g-1dry soil respectively,compared with tap water 4.45, 4.29 and 2.97 log cfu g-1dry soil respectively. Results showed also significantly increment in the number of pathogenic bacteria with increase rate of dry sludge utilized to soil. The rate 60 ton.ha-1 was the highest number of pathogenic bacteria in soil 6.21, 5.78 and 5.24 log cfu g-1dry soil respectively. Results showed reduced in the number of pathogenic bacteria in composting sludge compared with non-composting sludge, with reduced proportion of 9.78 , 6.67 and 8.50 % respectively.